Have Public Interests Been Forgotten in NAFTA Chapter 11 Foreign Investor/Host State Arbitration - Some Conclusions from the Judgment of the Supreme Court of British Columbia on the Case of Mexico v. Metalclad (2002)
United Mexican States v. Metalclad Corp. (Mexico v. Metalclad) constitutes a landmark decision regarding both arbitration under NAFTA Chapter 11 and review proceedings of NAFTA Chapter 11 arbitral awards. For the first time since their creation in 1978, the Additional Facility Rules of the International Center for the Settlement of Investment Disputes (ICSID) have governed an international arbitration.' In addition, the case exhibits the first time an arbitration award under NAFTA Chapter 11 has been challenged in a national court as provided for in article 1136.3(b)(i).